Urinary Schistosomiasis in two family populations, using school children as tracers - Anigbo, E.U.; Nwaorgu, O.C. (My University, 1988)
Two groups of families designated A and B were studied for Schistosoma haematobium infection in Amagunze, Anambra State, Nigeria. The groups were selected on the basis of a preliminary screening of schoolchildren: group A were children with negative urine samples and group B were those with positive samples. Each group contained 60 children and the families of each of these were screened for schistosomiasis. The total prevalence among the 1017 individuals examined was 48.4% and the mean egg count was 72/10 ml urine. The peak prevalence (73%) and intensity of infection (84 eggs/10 ml of urine) occurred between the ages of 5 and 14 years. The prevalence and intensity of S. haematobium infection was statistically higher in males than in females. Although water contact patterns were similar, families in group B were significantly more infected (59%) than those in group A (36%).
Keywords: chistosoma haematobium